165 PERSEPSI KARYAWAN TERHADAP KEBUTUHAN AFILIASI DENGAN KOMITMEN ORGANISASI PADA PERHOTELAN DI BALI - Putera, Benny Sedana; Indrawati, Komang Rahayu (Jurnal Psikologi Udayana, 2016)
The tourism sector is a favorite and seeded sector in Bali. That situation make many hotels in Bali compete with other hotels to give best service and best quality accommodation for tourist who came to Bali. In hotels, to give best service for tourist, the hotels need employee who has good skill and strong organizational commitment. Beside of that, how the employee have a perception about need for affiliation being important factor to interact with coworker in organization for reach the goal of hotels. The purpose of this research is to find the relationship between the perception of the need for affiliation with organizational commitment at hotels in Bali.This research use the quantitative method. The sampling technique that used in this research is a cluster sampling. This research use 128 respondent who work in hotel. Measure instrument in this research use scale perception of the need for affiliation with 59 item total and scale of organizational commitment with 42 item total. The coefficient of reliability for scale perception of the need for affiliation is 0,950 and for scale of organizational commitment is 0,958.Data in this research analyzed by simple linier regression with computer software SPSS version 15.0. The result of this research obtained that correlation coefficient is 0,715 with probability score is 0,000 (p<0,05). Based on the result can indicated there are significant relationship between the perception of the need for affiliation with organizational commitment. Determination coefficient (R2) which obtained in this research is 0,511 can be interpreted that perception of the need for affiliation have 51,1% can explain toward commitment organizational.Keyword: Perception of the need for affiliation, organizational commitment and hotel